Estudio De Factibilidad Para La Implementación De Una Empresa Productora De Maíz Pelado En Catamayo Y Su Comercialización En La Ciudad De Loja” - Morocho Calderón, Andrea Carolina (2016)
The project aims to contribute to run society in the growth and development of small industries and in turn to the local economy, developing a natural product of the basic value-added, as it has been since our ancestors as part of the food diet peeled corn (Zea Mays), offering an alternative to local families who have a hygienically processed ingredient for preparing various culinary dishes and give a good flavor when consumed bringing a quality product to your table , since corn is used for human consumption in white or yellow grains, providing an alternative healthy and natural flavor. The research project starts with a general topic called: Feasibility Study for the Implementation of a Bare Corn Production Company in Catamayo and marketing in the City of Loja, which raised specific objectives that served as a guide for the study: such as Market Research, Technical, Administrative and Financial. In addition to meeting the objectives used methods, techniques and tools that allowed for the deduction and induction in each project phase : Deductive allowed based on the theoretical concepts related to the realization of the investment project applied in the development of studies Market , Technical , Administrative , Financial and Financial Evaluation , Inductive : used in the particular development found in Project Feasibility generalizing conclusions and recommendations. We applied the following techniques : Through the interview was known dynamics peeled corn trade in the market, as they were applied to the 97 wineries dedicated to selling this product in bulk in the city of Loja , the survey was conducted plaintiffs who was a representative population of families from the city of Loja to determine the needs and preferences of the target market in relation to consumption of peeled corn ( Zea Mays ) , information vital to the establishment of the demand, supply and unmet demand product to work . The market research company finds that it is feasible to implement it according to the data obtained is unmet demand kilos of peeled corn 780.889 for the first year, the capacity utilization will cover 24% of the unmet demand, ie 144. 362 kilos for year 1. Investment reaches an amount of $ $ 37.870,93 in which 60% will be external capital and 40% of equity. At the point of balance for the first year allowed to know that the company will use an installed capacity of 74,05% and sales of $ 150.221,79 dollars for the company does not win or lose. Through the financial evaluation indicates that the MARR is Acceptable Minimum Rate of Return of the project is 17%, the NPV is positive equivalent of $ 99.701,90, an IRR of 75,32% which exceeds the rate of opportunity in the financial market, the company likewise recover their capital in two years, two month and 12 days and for every dollar the company earns 0.30 cents, according to the given conditions of the project in the sensitivity analysis supports an increase in costs of 15,91% and a decrease in revenue of 12,65%. Based on the results given it is recommended to implement the project as it will give significant returns for its investors and generates productive development as well as sources of employment increases and hence socio-economic development in the city of Loja province in general .